A conceptual framework for business intelligence critical success factors. (2019) - Jahantigh, Farzad Firouzi; Habibi, Arash; Sarafrazi, Azam
From theoretical and practical viewpoints, business intelligence application is considered by scholars and managers in their organisations. Most organisations are seeking to develop their capabilities and to gain a sustainable competitive advantage through business intelligence. Previous studies are mostly descriptive and they have emphasised the importance of business intelligence. This study aims to provide a conceptual framework for the assessment of business intelligence critical success factors in the organisations. The study was a pure research, which was conducted based on scientific research method and a five-year application of business intelligence in different organisations. The scale validity was approved using confirmatory factor analysis. The statistical data was also collected from 78 large and medium-sized companies. In this study, consistent with scientific research method principles, an operational scale is presented for the implementation of business intelligence. The results indicate that a suitable software and hardware platform is one of the most significant technical infrastructures for business intelligence implementation.